Crop diversification with castor (Ricinus communis L.) for enhancing the productivity, profitability and resource conservation under rice based cropping system: CROP DIVERSIFICATION WITH CASTOR UNDER RICE BASED CROPPING SYSTEM - P KATHIRVELAN; S MANICKAM; S R VENKATACHALAM; P ARUTCHENTHIL; M DEIVAMANI (Journal of Oilseeds Research, 2017)
On-farm experimental trials were conducted to find out the efficient, productive and remunerative crop in the existing rice based cropping systemfor sustaining the productivity and conserving natural resources inCauvery delta region of Tamil Nadu during summer 2015 and kharif 2015. The experiments were laid out in randomized block design and replicated four times with the following cropping sequence viz., rice -rice, rice - blackgram, rice - cotton, rice -sesame, rice - maize and rice - castor. The results revealed that the productivity ofsucceeding rice during kharif 2015 was significantly higher (5.85 t/ha) with rice - castor system while the lowest rice productivity was recorded under rice - rice (5.25 t/ha) cropping system. System productivity in terms of rice equivalent yield was significantly higher (14.1 t/ha) in rice - cotton systemfollowed byrice-blackgram, rice-maize and rice-castor. Significantly higher total biomass addition of 15.5 t/ha was recorded under rice-castor cropping system which was followed by rice-cotton cropping system (10.8 t/ha) which directly influenced organic carbon content (0.46 %), biomass carbon (598 mg/kg) which in turn improved bulk density (1.30). The highest net returns of `121360/ha and higher benefit : cost ratio of 3.1 was realized under rice-castor cropping system.